2019
DOI: 10.1016/j.jhep.2018.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Kupffer cell depletion in diethylnitrosamine-induced hepatic inflammation

Abstract: Recent evidence published in the Journal of Hepatology shed light on the fate of Kupffer cells (KCs) during hepatic inflammation. The study by Borst et al. elegantly demonstrated that KCs are rapidly depleted and then replaced by monocyte-derived macrophages in the course of viral hepatitis. 1 This report is quite in contrast to the dogma that KCs, as resident tissue macrophages, are self-maintaining cells. Similar observations were reported for hepatic inflammation induced by paracetamol, CCl 4 , or bacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…[2][3][4] In response to these findings, and to an Editorial in the Journal of Hepatology 5 questioning whether this pattern is observable in all liver diseases, Kessler et al published their experience in the diethylnitrosamine (DEN) model of hepatocarcinogenesis. 6 They showed that, despite a decrease in the ratio of macrophages over monocytes, the number of hepatic macrophages (defined as CD11b + CD11c À NK1.1 À Ly6G -Ly6C lo F4/80 hi cells) remained stable after short-term exposure to DEN, while both monocytes and macrophages were increased in the liver 22 weeks after DEN injection. The authors interpreted this as a lack of KC depletion in both the acute and chronic liver injury model.…”
Section: Unveiling the Depletion Of Kupffer Cells In Experimental Hepmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] In response to these findings, and to an Editorial in the Journal of Hepatology 5 questioning whether this pattern is observable in all liver diseases, Kessler et al published their experience in the diethylnitrosamine (DEN) model of hepatocarcinogenesis. 6 They showed that, despite a decrease in the ratio of macrophages over monocytes, the number of hepatic macrophages (defined as CD11b + CD11c À NK1.1 À Ly6G -Ly6C lo F4/80 hi cells) remained stable after short-term exposure to DEN, while both monocytes and macrophages were increased in the liver 22 weeks after DEN injection. The authors interpreted this as a lack of KC depletion in both the acute and chronic liver injury model.…”
Section: Unveiling the Depletion Of Kupffer Cells In Experimental Hepmentioning
confidence: 99%
“…Furthermore, they pointed to the characterization of macrophages and infiltrating monocytes in experimental hepatocellular carcinoma (HCC) as an outstanding research question. 6 The hepatic macrophage population consists of different subsets, however, which could not be distinguished using the set of markers employed by Kessler et al 6 Depletion of KCs following an acute insult is indeed well-established, 3 while the composition of liver monocytes/macrophages during DEN-induced HCC, and hepatic carcinogenesis in general, is less clear.…”
Section: Unveiling the Depletion Of Kupffer Cells In Experimental Hepmentioning
confidence: 99%
“…The ArC amine‐reactive compensation kit (Invitrogen, #A10346), anti‐rat/hamster beads (BD Biosciences, #552845), or anti‐mouse plus beads (BD, #560497) were used to generate compensation controls. All gates were set by using the appropriate fluorescence minus one (FMO) control (Kessler et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…5 While we and others discovered a rapid KC loss upon infection, 6,7 this phenomenon was initially not detected in diethylnitrosamine (DEN)-induced hepatocellular carcinoma (HCC). 8 In contrast, KC loss was apparent in 2 other HCC models. 5 These observations led to the question of whether KC loss after liver injury is a general phenomenon, or whether the KC fate is dependent on the nature of the liver insult.…”
mentioning
confidence: 96%
“…[12][13][14] While, KC classification under homeostatic conditions is well established, we and others discovered that under inflammatory con-ditions KC classification is more challenging ( Table 1). 4,6,8 Using the recently identified tissue-resident macrophage marker Tim4, Lefere et al followed up on the question of whether the local KC pool is depleted upon acute acetaminophen (APAP)induced liver injury and chronic inflammation. In accordance with previous data, they detected a profound KC loss during both, acute and chronic liver inflammation.…”
mentioning
confidence: 99%